Pengembangan Usaha Keripik Pisang UMKM Bernad Di Kelurahan Buraen Melalui Pemanfaatan Webside Dan Toko Online - Priyono, Priyono; Suprapto, Edy; Fahrizal, Fahrizal; K, Basri; Bianome, Wolfrid; Mau, Sealtiel (Abdi Masyarakat, 2023)
This article discusses the development of Bernard's banana chips small and medium-sized enterprise (UMKM) in Buraen Village through the utilization of a website, online store, and social media. This is based on the situation and role of UMKM as the backbone of the national economy. While UMKM has made significant contributions, many still struggle to compete globally in modern marketing. This integrated business development is aimed at one of the UMKM actors, specifically Bernard's UMKM in Amarasi Village, to optimize the production of chips and various pastries. The methods used include product development, trials, socialization, and training. The results of the community engagement show that the UMKM Bernard community is very enthusiastic, and even the village government participated in this training activity. The engagement team successfully developed a website integrated with an online store and social media to expand the marketing network of UMKM Bernard's products. The community's response to the website product was 83.8%, to the online store product was 91.9%, and to the social media promoting UMKM Bernard's products was 93.3%. The training results indicate that the managers of UMKM Bernard are capable of customizing and managing the website, online store, and social media. It is hoped that continuous training, monitoring, and mentoring will be conducted until the UMKM community becomes independent and capable of managing such technology themselves